RNA sequencing data from patients with heart disease and controls - Rotter Sopasakis, Victoria; Mattsson Hultén, Lillemor (University of Gothenburg, 2023)
RNA sequencing analysis of atrial cardiac tissue from patients undergoing coronary artery bypass grafting (CABG) or aortic valve replacement (AVR) was performed and compared with atrial cardiac tissue from organ donors and purchased human atrial cardiac RNA.

RNA sequencing analysis was performed at the Genomics Core Facility at University of Gothenburg, Sweden. All samples (ten controls, ten CABG patients and ten AVR patients) were quality checked by the RNA integrity number (RIN) using Tapestation 2200 RNA screenTape (Agilent Technologies, Santa Clara, CA) and RNA concentration was measured by NanoDrop (Thermo Fisher, Waltham, MA). RIN values ranged between 6.6 and 9.0 for all samples. TruSeq Total Stranded RNA kit with RiboZero (Gold) Sample Preparation Guide (15,031,048 Rev. E) was used for RNA sample preparation (Illumina, San Diego, CA). A total of 10 μl (~1 μg) RNA from each sample was used for library preparation. Directly after depletion, a cleanup step was performed using 110 ul of the RNAClean XP beads (Beckman Coulter, USA) for each sample. The fragmentation step was performed for 8 min. 12 PCR cycles were run for all samples. Libraries were quantified and normalized with Qubit DNA HS Assay kit (Life Technologies, Carlsbad, CA) and fragment size determined by Tapestation 2200 (Agilent Technologies, Santa Clara, CA). The libraries were pooled together by using the Illumina protocol for pooling and sequenced with NovaSeq 6000 S1 (Illumina, San Diego, CA) for the read length of 2 × 100 bp.

Data i denna studie kommer från RNA-sekvenseringsanalys av förmaksvävnad från humana hjärtan från patienter som genomgick coronary artery bypass grafting (CABG) eller aortic valve replacement (AVR) samt förmaksvävnad från organdonatorer (kontroller) och inköpt humant RNA från förmaksvävnad (kontroller).
RNA-sekvenseringsdata från patienter med hjärtsjukdom och kontroller
Keywords: Heart Diseases; Hjärtsjukdomar; Aortic Valve; Aortaklaff; Coronary Artery Bypass; Koronar bypass; Cadherins; Kadheriner; Heart Valve Prosthesis Implantation; Hjärtklaffprotesimplantation; RNA, Long Noncoding; Långt icke-kodande RNA; Cadherin Related Proteins; Kadherinrelaterade proteiner; Genetics and Genomics; Genetik och genomik; Bioinformatics and Computational Biology; Bioinformatik och beräkningsbiologi; Basic Medicine; Medicinska och farmaceutiska grundvetenskaper; Medical Genetics and Genomics; Medicinsk genetik och genomik; Cell and Molecular Biology; Cell- och molekylärbiologi; Cardiology and Cardiovascular Disease; Kardiologi och kardiovaskulära sjukdomar; Molecular Biology; Molekylärbiologi